Security analysis of weighted network anonymity based on singular value decomposition - Yong ZENG; Lingjie ZHOU; Zhongyuan JIANG; Zhihong LIU; Jianfeng MA (Tongxin xuebao)
The security of anonymous method based on singular value decomposition (SVD) in the privacy preserving of weighted social network was analyzed.The reconstruction method in network with integer weights and the inexact reconstruction method in network with arbitrary weighted were proposed.The ε N -tolerance was definited to measure its safety.It was also pointed out that the upper bound of ε (the reconfigurable coefficient) obtained in current spectral theories was so conservative that lacks of guidance.The reconfigurable coefficients of random networks,Barabasi-Albert networks,small world networks and real networks were calculated by experiment.Moreover,the reconfigurable coefficients of double perturbation strategies based on SVD were also tested.Experimental results show that weighted social networks have different tolerances on spectrum loss,and there is a close relationship between its tolerance and network parameters.